Biodrying of Sewage Sludge: Kinetics of Volatile Solids Degradation Under Different Initial Moisture Contents and Air-Flow Rates - Huilinir-Curio, C (Elsevier Ltd, 2014)
This study focuses on the kinetics of the biodegradation of volatile solids (VS) of sewage sludge for biodrying under different initial moisture contents (Mc) and air-flow rates (AFR). For the study, a 32 factorial design, whose factors were AFR (1, 2 or 3L/minkgTS) and initial Mc (59%, 68% and 78% w.b.), was used. Using seven kinetic models and a nonlinear regression method, kinetic parameters were estimated and the models were analyzed with two statistical indicators. Initial Mc of around 68% increases the temperature matrix and VS consumption, with higher moisture removal at lower initial Mc values. Lower AFRs gave higher matrix temperatures and VS consumption, while higher AFRs increased water removal. The kinetic models proposed successfully simulate VS biodegradation, with root mean square error (RMSE) between 0.007929 and 0.02744, and they can be used as a tool for satisfactory prediction of VS in biodrying. © 2014 Elsevier Ltd.